The pfeiffer book of successful leadership development tools (Pfeiffer, 2003)
Includes an overview of management theorists who have shaped modern thought about organizations and leadership, Contains complete, ready-made training exercises designed to meet a variety of needs for different audiences, Offers inventories that include questionnaires and instruments that help people clarify their own beliefs about leadership